Treatment of inguinal hernias Plasty vs. Raffia: Police Hospital Experience - Fernández, Alvaro; Payssé, Ignacio; Sánchez, Luis F; Kenny, Juan (Cirugía del Uruguay, 2006)
Retrospective analysis of inguinal herniations operated in the Police Hospital over a 17-year period. Results led to comparing herniorraphies with hernioplaties. This study shows that overall results in our Service have been good with the various techniques for inguinal herniorraphias, recurrence rate being 8,2%. Nonetheless, better results were obtained with hernioplaties, recurrence rate being 1,5% and morbidity being similar.